Identification of biomarkers to measure HIV-specific mucosal and systemic CD8+ T-cell immunity using single cell Fluidigm 48.48 Dynamic arrays. Issue 51 (16th December 2015) - Trivedi, Shubhanshi; Neeman, Teresa; Jackson, Ronald J.; Ranasinghe, Roshanka; Jack, Cameron; Ranasinghe, Charani
Highlights: RANTES, MIP-1β, perforin, α4, β1 and β7: set of biomarkers to measure HIV-specific mucosal immunity. Intensity of IL-13 inhibition can modulate the level of poly-functionality and CTL immunity. According to the anatomical location immune markers expressed can be significantly different. According to the anatomical location Em and Cm T cell ratios can be significantly different. Fluidigm 48.48 dynamic array is an effective tool to measure vaccine-specific mucosal immunity. Abstract: Thirty genes composed of cytokines, chemokines, granzymes, perforin and integrins were evaluated in gut and splenic K d Gag197–205 -specific single CD8 + T cells using Fluidigm 48.48 Dynamic arrays, with the aim of identifying biomarkers to predict effective mucosal and systemic vaccine efficacy. The mRNA expression profiles were analyzed in three ways: (i) the "number" of K d Gag197–205 -specific CD8 + T cells expressing the biomarker, (ii) "level" of mRNA expression using principal component analysis (PCA) and (iii) poly-functionality in relation to RANTES expression. In total, 21 genes were found to be differentially expressed between the vaccine groups and the immune compartments tested. Overall, the PCA indicated that IL-13Rα2 or IL-4R antagonist adjuvanted vaccines that previously induced high-avidity mucosal/systemic CD8 + T cells with better protective efficacy, the "level" of mRNA expression, specifically RANTES, MIP-1β, and integrin α4 in gut K d Gag197–205 -specific single CD8 + T cells, were significantly elevated compared to unadjuvanted vaccine. Furthermore, significantly elevated granzymes/perforin levels were detected in IL-13 −/− mice given the unadjuvanted vaccine, indicating that the degree of IL-13 inhibition (total, transient or no inhibition) can considerably alter the level of T-cell activity/poly-functionality. When splenic- and gut-K d Gag197–205 -specific CD8 + T cells were compared, PC1 vs. PC2 scores revealed that not only RANTES, MIP-1β, and integrin α4 mRNA, but also perforin, granzymes A/B, and integrins β1 and β2 mRNA were elevated in spleen. Collectively, data suggest that RANTES, MIP-1β, perforin, and integrins α4, β1 and β7 mRNA in single HIV-specific CD8 + T cells could be used as a measure of effective mucosal and systemic vaccine efficacy.